2013
DOI: 10.4236/aid.2013.34042
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS-Related Knowledge among Secondary School Students in Bangladesh: A Cross-Sectional Study

Abstract: Background and Aim of the Study: HIV/AIDS is best viewed as a major epidemic which poses serious challenges to mankind on a global scale. The aim of this study was to assess the HIV/AIDS-related knowledge among secondary school students in Bangladesh and investigate the association between secondary school students' socio-demographic characteristics and their level of knowledge about HIV/AIDS. Methods: Following multistage random sampling technique, a total of 384 students aged 11 -17 years were sampled from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
2
13
2
Order By: Relevance
“…Studies found that primary sources of information for students about HIV/AIDS were the print and electronic media [1423, 31], whereas textbooks, and teachers were the next important sources of information [20, 23]. In this current study however, no notable differences were found among students from both the control and intervention areas, in regards to exposure to TV/radio/newspaper.…”
Section: Discussioncontrasting
confidence: 68%
“…Studies found that primary sources of information for students about HIV/AIDS were the print and electronic media [1423, 31], whereas textbooks, and teachers were the next important sources of information [20, 23]. In this current study however, no notable differences were found among students from both the control and intervention areas, in regards to exposure to TV/radio/newspaper.…”
Section: Discussioncontrasting
confidence: 68%
“…and higher secondary institution-based HIV/AIDS education is a common and well-proven intervention strategy for providing information on HIV/ AIDS to students. Young people including students are at the centre of the HIV epidemic; almost half of all HIV-infected people are aged 15-24 years across the world (Huda & Amanullah 2013;. Therefore, HIV/AIDS education through FCT can be considered one of the best mediums of disseminating information among students.…”
Section: Secondarymentioning
confidence: 99%
“…First, the students in Bangladesh are susceptible to HIV and STDs. However, they lack useful information about the taboo subject (Huda, 2013;Huda & Amanullah, 2013). Second, students and teachers in Bangladesh, a predominantly conservative Muslim society, are very reluctant to talk to each other about HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…High school students’ knowledge about HIV/ AIDS might be varies by their socio-demographic characteristics such as age, gender, school type, family head income, fathers’ and mothers’ educational levels, and source of information. The study of knowledge of HIV/AIDS is considered a basic first step in the education process and prevention of the disease ( Huda & Amanullah, 2013 ).…”
Section: Introductionmentioning
confidence: 99%